2023
DOI: 10.3389/fpsyg.2023.989711
|View full text |Cite
|
Sign up to set email alerts
|

Personality characteristics, defense styles, borderline symptoms, and non-suicidal self-injury in first-episode major depressive disorder

Abstract: BackgroundNon-suicidal self-injury (NSSI) is commonly seen in adolescents with depression and is a high-risk factor leading to suicide. The psychological mechanisms underlying depression with NSSI are still unclear. The purpose of this study was to explore the differences in personality traits, defensive styles, and borderline symptoms among first-episode youth patients with depression and self-injury compared with patients with depression without self-injury and healthy populations.MethodsThe current study re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…Our finding suggested that patients with depression are more likely to use immature and intermediate defense mechanisms, and less likely to use mature defense mechanisms, which is consistent with the case–control study by Peng et al ( 45 ) conducted in populations with depression and non-suicidal self-injury. Accumulating literatures suggest that depressed patients mainly tend to use immature defense mechanisms ( 46 , 47 ).…”
Section: Discussionsupporting
confidence: 91%
“…Our finding suggested that patients with depression are more likely to use immature and intermediate defense mechanisms, and less likely to use mature defense mechanisms, which is consistent with the case–control study by Peng et al ( 45 ) conducted in populations with depression and non-suicidal self-injury. Accumulating literatures suggest that depressed patients mainly tend to use immature defense mechanisms ( 46 , 47 ).…”
Section: Discussionsupporting
confidence: 91%
“…The Psychoticism domain of the PID-5 includes traits such as Unusual Beliefs & Experiences, Eccentricity, and Perceptual Dysregulation (74). According to Peng et al, patients with depression and NSSI have significantly higher levels of psychoticism than healthy controls and patients with depression alone (73). In addition, regression analysis showed that psychoticism was an independent risk factor for NSSI in depressed patients.…”
Section: Correlations Between Nssi Functions and Personality Traitsmentioning
confidence: 99%
“… 18 It has been reported that compared to simple depression, comorbidity will characterize more severe clinical phenotypes in adolescents, aggravate the psychological and disease burden of patients, and increase the risk of suicide. 19 Previous research on comorbidity of NSSI and depression in adolescents had focused on correlates, such as introversion, intermediate defenses, 20 youthfulness, and impulsivity, 21 but the specific symptoms underlying this correlation are still unclear.…”
Section: Introductionmentioning
confidence: 99%